Iatrogenic vocal process fracture and arytenoid dislocation caused by transesophageal echocardiography - (:unkn) unknown (My University, 2016)
Aritenoid dislokasyonu (AD) larengeal travmaya sekonder gelişebilen nadir bir durumdur. Aritenoid dislokasyonu ile birlikte olan vokal proses kırığına tanı koymak için fiberoptik larengoskopi, larengeal bilgisayarlı tomografi ve larengeal elektromiyografi kullanılır. Bu yazıda, transözofageal ekokardiyografiden sonra ses kısıklığı olan 26 yaşında bir kadın hasta sunuldu. Eşlik eden AD ve vokal proses kırığı tanısıyla kapalı redüksiyon uygulandı. Üst solunum yolu ve sindirim sisteminde enstrüman kullanılan ve özellikle AD tanısı konulup redüksiyon işlemlerine yanıt vermeyen tüm hastalarda kapalı redüksiyon düşünülmelidir.

Arytenoid dislocation (AD) is a rare condition that may occur secondary to laryngeal trauma. Fiberoptic laryngoscopy, laryngeal computed tomography, and laryngeal electromyography are used to diagnose vocal process fracture in conjunction with AD. In this article, we report a 26-yearold female patient with hoarseness after transesophageal echocardiography. With the diagnosis of concomitant AD and vocal process fracture, closed reduction was performed. Closed reduction should be considered for all patients in whom instruments have been used in the upper aerodigestive tract and particularly who are diagnosed as AD and non-responsive to reduction procedures.
Transözofageal ekokardiyografinin neden olduğu iyatrojenik vokal proses kırığı ve aritenoid dislokasyonu
Keywords: Kulak, Burun, Boğaz